Isfahan University of Technology (IUT): Towards a Green Campus Energy, Climate and Sustainable Development Initiatives at IUT - S. M Abtahi (Universitas Diponegoro, 2021)
Today, many universities are trying to move towards sustainability by observing the principles of environment and green management. In this regard, the issue of green university has been considered by many countries in recent years, and many efforts have been made to join (UIGWURN (UI GreenMetric World University Rankings Network)). Isfahan University of Technology (IUT), as one of the top higher education universities in Iran, has taken fundamental steps to implement